The COPRA experiments on the in-vessel melt pool behavior in the RPV lower head. (March 2016) - Zhang, Y.P.; Zhang, L.T.; Zhou, Y.K.; Tian, W.X.; Qiu, S.Z.; Su, G.H.; Zhao, B.; Yuan, Y.D.; Ma, R.B.
Highlights: Establishing the first full-scale COPRA facility for Chinese PWR. New experiments can be conducted using COPRA facility. The first experimental results of COPRA were discussed. Abstract: The COPRA (COrium Pool Research Apparatus) facility was designed to investigate the in-vessel molten corium pool behavior for the in-vessel corium retention during severe accidents in Chinese large-scale advanced PWRs. The main part of the COPRA facility is a two-dimensional 1/4 circular slice test section with an inner radius of 2.2 m to simulate the lower plenum of the reactor vessel at 1:1 scale for the Chinese large-scale advanced PWR. Up to now, the COPRA experiments have been performed in different melt volumes, heat generation rates and multiple injection of the melt in the one test. At present, the well-known simulant material NaNO3 –KNO3 in non-eutectic composition (20 mol% NaNO3 –80 mol% KNO3 ) is used. This work presents the behavior of a large-scale homogenous melt pool regarding the melt pool temperature, heat flux distribution through the vessel wall and crust thickness in transient and steady state conditions. And the heat transfer towards the vessel wall of the COPRA test was compared with previous experiments and experimental correlations. It showed that the downward heat transfer from the COPRA experiments was lower than those from other experiments within the same range of Rayleigh numbers (10 15 –10 17 ).